A Brief Review: Some Interesting Methods of Synthesis Chromene Derivatives as Bioactive Molecules - Zainab Sallal Abdulsahib; Raied Mustafa Shakir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Chromene is considered a fused pyran ring with a benzene ring, which is found in many plants and is part of many important compounds such as anthocyanidins, anthocyanins, catechins, and flavanones. These compounds are included under the headings "flavonoids" and "iso-flavonoids." These compounds are well known as bioactive molecules with wide medicinal uses. According to these pharmacokinetic characteristics, many researchers are giving more attention to this type of compound and its derivatives. Many chromene derivatives have been synthesized to study their biological effects for the treatment of many diseases. Furthermore, the researcher displayed wide interest in finding new methods for synthesizing chromene derivatives. These methods depend on utilizing a new catalyst to increase the yield of this reaction or reduce the time of the reaction. On the other hand, new methods were found by using a new reactant and a new substrate. This review will present the most recent important methods for the synthesis of chromene derivatives as well as an examination of their biological activity.